Europium(III) Meets Etidronic Acid (HEDP): A Coordination Study Combining Spectroscopic, Spectrometric, and Quantum Chemical Methods - Anne Heller; Christian Senwitz; Harald Foerstendorf; Satoru Tsushima; Linus Holtmann; Björn Drobot; Jerome Kretzschmar (Molecules, 2023)
Etidronic acid (1-Hydroxyethylidene-1,1-diphosphonic acid, HEDP, H4L) is a proposed decorporation agent for U(VI). This paper studied its complex formation with Eu(III), an inactive analog of trivalent actinides, over a wide pH range, at varying metal-to-ligand ratios (M:L) and total concentrations. Combining spectroscopic, spectrometric, and quantum chemical methods, five distinct Eu(III)−HEDP complexes were found, four of which were characterized. The readily soluble EuH2L+ and Eu(H2L)2− species with log β values of 23.7 ± 0.1 and 45.1 ± 0.9 are formed at acidic pH. At near-neutral pH, EuHL0s forms with a log β of ~23.6 and, additionally, a most probably polynuclear complex. The readily dissolved EuL− species with a log β of ~11.2 is formed at alkaline pH. A six-membered chelate ring is the key motif in all solution structures. The equilibrium between the Eu(III)–HEDP species is influenced by several parameters, i.e., pH, M:L, total Eu(III) and HEDP concentrations, and time. Overall, the present work sheds light on the very complex speciation in the HEDP–Eu(III) system and indicates that, for risk assessment of potential decorporation scenarios, side reactions of HEDP with trivalent actinides and lanthanides should also be taken into account.